Jaipur Foot: An Attempt to Replicate Jaipur Model in Surat City - Mahida, Hetavi; Mahida, Dhiren (National Journal of Community Medicine, 2015)
The Jaipur limb has revolutionized the treatment of amputees in India costs only about 30 compared to a prosthetic foot in the U.S. costing 8,000. Jaipur limb is given away free to the many handicapped poor who have lost a limb. The attempt was made to replicate the model on a smaller scale without any financial help from others in a small private hospital in Surat is presented. The manufacturing process of the Jaipur foot, its advantages and drawbacks, its cost, the short coming in the project and possible reasons of inability to sustain the project is presented here.